2016
DOI: 10.1002/mnfr.201600338
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 improves cardiac dysfunction, hypertrophy, and fibrosis through PARP1/SIRT1/mTOR‐related mechanisms in type 1 diabetes

Abstract: The present study demonstrates that 1,25(OH) D treatment has the potential to improve diabetic cardiomyopathy in rats and suggests that VD-VDR signaling induces this protective effect against diabetic cardiomyopathy might partly through the PARP1/SIRT1/mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Previously, studies have shown that SIRT1 negatively regulated mTOR signaling in a variety of cells, such as MEFs cells, HeLa cells and cardiomyocytes [48,49]. In the current work, we showed that SIRT1 mediated mTOR signaling in response to high glucose in neurons, evidenced by SIRT1 agonist resveratrol inhibited high glucose-induced phosphorylation of mTOR in HT-22 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Previously, studies have shown that SIRT1 negatively regulated mTOR signaling in a variety of cells, such as MEFs cells, HeLa cells and cardiomyocytes [48,49]. In the current work, we showed that SIRT1 mediated mTOR signaling in response to high glucose in neurons, evidenced by SIRT1 agonist resveratrol inhibited high glucose-induced phosphorylation of mTOR in HT-22 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Increased expression of connective tissue growth factor (CTGF), TGF-β1, SMAD3, poly [ADP-ribose] polymerase 1 (PARP1), sirtuin 1 (SIRT1), and mechanistic target of rapamycin (mTOR) in diabetes mediate cardiac fibrosis [6163]. The negative regulation of the activity of TGF-β1, SMAD3, CTGF, and PARP1/SIRT1/mTOR pathway with vitamin D suggests the protective role of vitamin D on fibrosis [6366](Table 1). Wang et al [67] using the rat model reported that diabetes induces the cardiac weight index, plasma glucose, lactic dehydrogenase and creatine kinase with the reduced body and cardiac weights and pathological changes of fibrosis.…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…Current evidence shows that association of vitamin D and sirtuins may be through both direct and indirect pathways. Direct association of vitamin D with SIRT1, through vitamin D receptor (VDR), has been shown in experimental models [39][40][41]. On the other hand, vitamin D-induced upregulation of SIRT1 together with pAMPK and GLUT-4 in adipose tissue suggests a role for these insulinindependent signaling molecules in glycemic control through vitamin D [38].…”
Section: Discussionmentioning
confidence: 99%